3D printing ink, composite hydrogel scaffold, preparation method and application thereof

By using strontium modified nano-concave and concave rock stone, methacrylylated hydrogel and chitosan, combined with Pickering emulsion technology and 3D printing technology, composite hydrogel scaffolds are prepared, which solves the challenges of existing 3D-printed bone repair materials in terms of mechanical properties, biological activity and controllability, and overcomes the shortcomings of traditional bone grafting methods to achieve an effective solution for bone defect repair.

CN119015490BActive Publication Date: 2025-04-25CHANGZHOU NO 2 PEOPLES HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410818661.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-04-25
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

Existing 3D printed bone repair materials have challenges in mechanical properties, biological activity and controllability, and traditional bone transplantation methods have problems such as insufficient donor sources, immune rejection and surgical complications.

Method used

The composite hydrogel scaffold is prepared by using strontium modified nano-concave and concave rock stone, methacrylylated hydrogel and chitosan, and the composite hydrogel scaffold is improved by Pickering emulsion technology and 3D printing technology to improve its mechanical properties and osteoinductive ability.

Benefits of technology

The preparation of composite hydrogel scaffolds with excellent biocompatibility and osteoinduction capabilities has been achieved, overcoming the shortcomings of traditional bone grafting methods, and providing a biodegradable tissue-engineered bone repair material suitable for bone defect repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119015490B_ABST
    Figure CN119015490B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of bone tissue engineering, and provides 3D printing ink, composite hydrogel scaffolds, and their preparation methods and applications. Among them, a 3D printing ink comprises strontium-modified nano-attapulgite, methacrylated hydrogel, a first phase solvent, a second phase solvent, a functional additive, and a photoinitiator. The composite hydrogel scaffold is prepared from 3D printing ink. The above 3D printing ink and composite hydrogel scaffold can be used for bone repair, improving its biological activity and bone induction ability, and composite hydrogel scaffolds with different pores, sizes and shapes can be prepared as needed. The scaffold has good biological activity, degradability, biocompatibility, bone induction ability, no toxic side effects, meets the requirements of tissue engineering materials, and has excellent clinical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of bone tissue engineering, and in particular to 3D printing ink, composite hydrogel scaffolds, and preparation methods and applications thereof. Background Art

[0002] Bone defect repair is an important issue in the medical field. Traditional treatment methods mainly include autologous bone transplantation and allogeneic bone transplantation. However, these methods have a series of problems, such as insufficient donor sources, immune rejection and surgical complications, which limit their clinical application. With the development of tissue engineering and biomaterials science, people have begun to explore new bone repair materials and methods. As an emerging repair method, tissue engineering bone materials have the potential to simulate natural bone structure and promote bone regeneration. However, current tissue engineering bone materials still have some challenges in terms of mechanical properties, bioactivity and controllability.

[0003] 3D printing technology provides a new solution in the field of bone repair. Through computer-aided design (CAD) and 3D printing technology, a three-dimensional structure that fully matches the patient's bone defect can be accurately constructed. 3D printing technology can use a variety of biomaterials (such as hydrogels, ceramics, metals and composites) to make porous scaffolds with complex geometries. These scaffolds can promote cell adhesion, proliferation and differentiation, thereby accelerating the regeneration of bone tissue.

[0004] However, existing 3D printed bone repair materials also have some disadvantages. Due to the limitations of printing accuracy and material properties, the porous scaffold structure of 3D printing may not be uniform and regular enough, which may affect its mechanical properties and biological functions; during the 3D printing process, the use of bio-ink containing large-sized solid particles may cause nozzle clogging, making it difficult to prepare large-pore hydrogel structures; although 3D printing technology can use a variety of biomaterials, the biocompatibility and mechanical properties of these materials still need to be further optimized to better support the proliferation and differentiation of bone and cartilage cells. Summary of the invention

[0005] The present invention aims to provide a 3D printing ink, a composite hydrogel scaffold, and their preparation methods and applications, which are used to construct a biodegradable tissue engineering bone repair material with mechanical strength and the ability to induce bone formation, so as to overcome the problems of insufficient donor sources, immune rejection reactions, and surgery-related complications existing in traditional methods.

[0006] To achieve the above objectives, according to one aspect of the present invention, a 3D printing ink is provided, comprising strontium-modified nano-attapulgite (Sr-ATP), methacrylated hydrogel (GelMA), a first phase solvent, a second phase solvent, a functional additive and a photoinitiator.

[0007] Nano-attapulgite (ATP) is a natural silicate nanomaterial with a chain-layered structure, and its structure belongs to a 2:1 type clay mineral. ATP has a series of excellent properties, including nanorod-like structure, high viscosity and plasticity, water absorption, multi-porous structure, strong adsorption and rich trace element content. Strontium (Sr) is a trace element that has been proven to promote osteoblast proliferation and new bone formation. It can act on bones through calcium-sensitive receptors and promote mitogen-activated protein kinase (MAPK) signal transduction. Strontium-modified nano-attapulgite further improves its biological activity and bone induction ability.

[0008] The hydrogel composite system is an effective strategy to combine multiple hydrogel functions and properties. The mechanical strength of the hydrogel can be improved by stabilizing and fixing the reinforcing materials through physical or chemical interactions in the hydrogel matrix. The mechanical properties of the pre-interpenetrating network hydrogel in bone tissue engineering can be improved by combining the above-mentioned raw materials, so that it can meet the needs of bone repair and is a biodegradable tissue engineering bone repair material that can induce osteogenesis.

[0009] Furthermore, the dosage ratio of the strontium-modified nano-attapulgite to the first phase solvent is 0.01-5g / ml, the dosage ratio of the methacrylated hydrogel to the second phase solvent is 0.01-0.5g / ml, the photoinitiator is a LAP photoinitiator, and the dosage ratio of the photoinitiator to the mixed solution of the methacrylated hydrogel and the second phase solvent is 0.002-0.1g / ml, the volume ratio of the mixed solution of the strontium-modified nano-attapulgite and the first phase solvent to the mixed solution of the photoinitiator, the methacrylated hydrogel and the second phase solvent is 0.1:1-2:1, and the functional additive is chitosan, and the dosage ratio of the functional additive to the above mixed raw materials is 0.001-1g / ml.

[0010] Furthermore, the first phase solvent is any one of dodecane, octane, decane, cyclohexane, tetradecane and hexadecane.

[0011] Furthermore, the second phase solvent includes phosphate-buffered saline (PBS) buffer.

[0012] According to another aspect of the present invention, a method for preparing a 3D printing ink is provided, comprising the following steps:

[0013] 1) according to the mass / volume fraction, 0.1 to 10 parts of strontium-modified nano-attapulgite powder are taken and dissolved in 10 to 500 parts of the first phase solvent, ultrasonically treated for 15 minutes to uniformly disperse the stable particles in the system, and stirred for 2 to 10 minutes to completely emulsify them;

[0014] 2) dissolving 0.1 to 10 parts of methacrylated hydrogel in 1 to 100 parts of the second phase solvent solution at 60° C., adding LAP photoinitiator in a ratio of 0.002 to 0.1 g / ml to the above mixed solution, and mixing and stirring for 30 to 60 minutes;

[0015] 3) Mix the above steps at a volume ratio of 0.1:1-2:1, and stir the mixed system for 2-10 minutes to completely emulsify it to obtain a water-in-oil Pickering emulsion;

[0016] 4) According to the mass / volume fraction, weigh 0.01 to 1 part of chitosan particles and add them to 1 to 10 parts of Pickering emulsion, and stir in a constant temperature water bath for 20 to 40 minutes.

[0017] Furthermore, the method further comprises the steps of preparing the strontium-modified nano-attapulgite powder:

[0018] According to the mass / volume fraction, weigh 1 to 50 parts of strontium chloride (SrCl 2 ) particles are dissolved in 1 to 400 parts of a nano-attapulgite suspension, stirred in a constant temperature water bath for 8 to 24 hours, uniformly mixed, and centrifuged to collect the strontium-modified nano-attapulgite particles, and the particles are rinsed in distilled water. After rinsing, AgNO is added to the suspension. 3 The test was carried out to remove the residual chloride ions, and the obtained product was dried at 100°C for two days and then crushed, and the product was digested to obtain strontium-modified nano-attapulgite powder. 2+ The strontium-modified nano-attapulgite powder generated by loading the nano-attapulgite can be used in the present invention.

[0019] Furthermore, the water used to dissolve the nano-attapulgite in the nano-attapulgite suspension is any one of deionized water, distilled water, phosphate buffer, and physiological saline. The nano-attapulgite is 200-500 nanometer-scale crystal particles. Pure water is used as the grinding medium, sodium hexametaphosphate is used as the grinding aid and dispersant, and the attapulgite powder is ground at a speed of 2000 rpm for 1-2 hours. The attapulgite crystals are fully dispersed through adsorption, electrochemical action and chemical reaction.

[0020] According to another aspect of the present invention, a composite hydrogel scaffold is prepared from the above-mentioned 3D printing ink.

[0021] According to another aspect of the present invention, a method for preparing a composite hydrogel scaffold comprises the following steps:

[0022] 1) 3D printing ink prints out the required scaffold: Design a printing program, and 3D printing ink is used to print out the composite hydrogel scaffold layer by layer through a CF-300N extrusion needle under basic parameters (needle diameter: 0.1-1 mm; pressure: 0.1-0.8 MPa; feed rate: 0.5-5 cm / min);

[0023] 2) cross-linking the printed scaffold with ultraviolet light of wavelength 360nm or 405nm for 10 to 100s to make the scaffold have a certain strength;

[0024] 3) placing the UV-crosslinked scaffold in a 0.05-0.2 mol / L crosslinking solution to continue crosslinking chitosan for 0.5-12 hours. After the reaction is completed, washing with anhydrous ethanol for multiple times to remove the oil phase, washing with ultrapure water for more than three times, and freeze-drying to obtain a porous strontium-modified attapulgite hydrogel scaffold (Sr-ATP / GelMA / CS), wherein the crosslinking solution is any one of sodium hydroxide, glutaraldehyde, glyoxal, and catalase.

[0025] Strontium (Sr) ions are introduced into nano-attapulgite (ATP) to form strontium-modified ATP particles to improve its biological activity and bone induction ability. Then, a hydrogel with a regular pore structure is prepared by Pickering emulsion technology. Specifically, strontium-modified ATP is used as a stable particle, dodecane solution is used as an oil phase, and methacrylated gelatin (GelMA) solution is used as an aqueous phase, and a water-in-oil high internal phase emulsion is prepared by Pickering emulsion method. Next, chitosan is introduced, and the emulsion is printed into a target scaffold by 3D printing technology. The chitosan phase is cross-linked by photo-crosslinking the GelMA phase and the crosslinking agent liquid to obtain a composite hydrogel scaffold with a certain mechanical strength and a connected pore structure. Finally, the oil phase is removed by multiple washings to obtain the final composite hydrogel scaffold. The composite hydrogel scaffold of the present invention has excellent biocompatibility and bone induction ability, is suitable for bone defect repair, solves the problems of insufficient donor sources, immune rejection and surgery-related complications of traditional bone transplantation methods, and has a wide range of clinical application prospects. The scaffold has good degradability, biocompatibility, no toxic side effects, and meets the requirements of tissue engineering materials.

[0026] According to another aspect of the present invention, the above-mentioned 3D printing ink, composite hydrogel scaffold or the 3D printing ink and composite hydrogel scaffold prepared by the preparation method are used in bone defect repair.

[0027] The beneficial effects achieved by the present invention are:

[0028] 1) The ATP used in the present invention is an environmentally friendly green material. The trace elements such as Si and Mg it contains have an important influence on the growth and regeneration of bones, and have good research value in bone tissue engineering applications. ATP has the characteristics of high viscosity and strong plasticity, and is suitable for 3D printing rapid prototyping. Strontium (Sr) is a trace element that has been proven to promote osteoblast proliferation and new bone formation. It can act on bones through calcium-sensitive receptors to promote mitogen-activated protein kinase (MAPK) signal transduction. Strontium-modified nano-attapulgite further improves its biological activity and bone induction ability. The hydrogel composite system is an effective strategy to combine multiple hydrogel functions and properties. The reinforcing material is stabilized and fixed by physical or chemical interactions in the hydrogel matrix to improve the mechanical strength of the hydrogel. The 3D printing ink of the present invention is a composite of the above-mentioned raw materials, which can improve the mechanical properties of the pre-interpenetrating network hydrogel in bone tissue engineering, so that it can meet the needs of bone repair and is a biodegradable tissue engineering bone repair material that can induce bone formation; the two immiscible solvent raw materials can be organically combined with 3D printing technology in the later stage to construct a porous Sr-Nano-ATP / GelMA / CS composite hydrogel raw material with good mechanical properties and bone induction characteristics.

[0029] 2) The present invention organically combines the Pickering emulsion template method with 3D printing technology to construct a porous Sr-Nano-ATP / GelMA / CS composite hydrogel repair material with good mechanical properties and bone induction properties, overcoming the poor regularity of the traditional preparation of porous scaffold structures and the difficulty in preparing large-pore hydrogel structures during 3D printing due to clogging by large-sized solid particles, thus meeting the demand for bone repair materials.

[0030] 3) The attapulgite hydrogel scaffold of the present invention has biodegradability and slowly releases Sr during the degradation process. 2+ Mg 2+ And Si 4+ etc., can jointly promote bone formation while still maintaining a certain mechanical support effect, thereby fundamentally repairing the defect.

[0031] 4) The attapulgite hydrogel scaffold of the present invention has good biocompatibility and bone induction ability, meeting the requirements of bone repair materials.

[0032] 5) The method for preparing the attapulgite hydrogel scaffold material of the present invention has mild process conditions, is easy to implement, has high dimensional accuracy, and good repeatability. Composite scaffolds with different sizes and shapes can be prepared as needed, and have excellent clinical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0034] Figure 1 This is a photo of the strontium-modified attapulgite hydrogel composite hydrogel scaffold of Example 1 of the present invention.

[0035] Figure 2 The front and side scanning electron microscope images of the microstructure of the strontium-modified attapulgite hydrogel composite hydrogel scaffold of Example 1.

[0036] Figure 3 This is a Live / Dead staining result of the co-culture of the strontium-modified attapulgite hydrogel composite hydrogel scaffold and cells in Example 1.

[0037] Figure 4 This is a graph showing the results of phalloidin staining of the strontium-modified attapulgite hydrogel composite hydrogel scaffold and cell co-culture in Example 1.

[0038] Figure 5 H&E staining images of tissue sections of comparative example 1 (blank group), comparative example 2 (not modified with strontium) and strontium-modified attapulgite composite hydrogel scaffolds of Example 5, respectively, after being implanted into animal bone defects for 2 months.

[0039] Figure 6 Masson staining images of tissue sections of comparative example 1 (blank group), comparative example 2 (not modified by strontium) and strontium-modified attapulgite composite hydrogel scaffolds of Example 5 after being implanted into animal bone defects for 2 months. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The invention provides a 3D printing ink, comprising strontium-modified nano-attapulgite, methacrylated hydrogel, a first phase solvent, a second phase solvent, a functional additive and a photoinitiator.

[0042] In the present invention, the dosage ratio of the strontium-modified nano-attapulgite to the first phase solvent is 0.01-5g / ml, the dosage ratio of the methacrylic hydrogel to the second phase solvent is 0.01-0.5g / ml, the photoinitiator is LAP photoinitiator, the dosage ratio of the photoinitiator to the mixed solution of the methacrylic hydrogel and the second phase solvent is 0.002-0.1g / ml, the volume ratio of the mixed solution of the strontium-modified nano-attapulgite and the first phase solvent to the mixed solution of the photoinitiator, the methacrylic hydrogel and the second phase solvent is 0.1:1-2:1, the functional additive is chitosan, and the dosage ratio of the functional additive to the above mixed raw materials is 0.001-1g / ml.

[0043] In the present invention, the first phase solvent is any one of dodecane, octane, decane, cyclohexane, tetradecane and hexadecane.

[0044] In the present invention, the second phase solvent includes phosphate buffer.

[0045] The present invention provides a method for preparing a 3D printing ink, comprising the following steps:

[0046] 1) according to the mass / volume fraction, 0.1 to 10 parts of strontium-modified nano-attapulgite powder are taken and dissolved in 10 to 500 parts of the first phase solvent, ultrasonically treated for 15 minutes to uniformly disperse the stable particles in the system, and stirred for 2 to 10 minutes to completely emulsify them;

[0047] 2) dissolving 0.1 to 10 parts of methacrylated hydrogel in 1 to 100 parts of the second phase solvent solution at 60° C., adding LAP photoinitiator in a ratio of 0.002 to 0.1 g / ml to the above mixed solution, and mixing and stirring for 30 to 60 minutes;

[0048] 3) Mix the above steps at a volume ratio of 0.1:1-2:1, and stir the mixed system for 2-10 minutes to completely emulsify it to obtain a water-in-oil Pickering emulsion;

[0049] 4) According to the mass / volume fraction, weigh 0.01-1 part of chitosan particles and add them to 1-10 parts of Pickering emulsion, and stir in a constant temperature water bath for 20-40 minutes. Preferably, the constant temperature water bath temperature is 30-60°C.

[0050] The present invention also includes the steps of preparing Sr-ATP powder:

[0051] According to the mass / volume fraction, weigh 1 to 50 parts of strontium chloride (SrCl 2) particles are dissolved in 1 to 400 parts of a nano-attapulgite suspension, stirred in a constant temperature water bath for 8 to 24 hours, uniformly mixed, and centrifuged to collect the strontium-modified nano-attapulgite particles, and the particles are rinsed in distilled water. After rinsing, AgNO is added to the suspension. 3 The test was conducted to remove the residual chloride ions, and the obtained product was dried at 100°C for two days and then crushed. The product was digested to obtain strontium-modified nano-attapulgite powder. Strontium-modified nano-attapulgite powder

[0052] In the present invention, the water used to dissolve the nano-attapulgite in the nano-attapulgite suspension is any one of deionized water, distilled water, phosphate buffer, and physiological saline. The nano-attapulgite is 200-500 nanometer-scale crystal particles. Pure water is used as a grinding medium, sodium hexametaphosphate is used as a grinding aid and dispersant, and the attapulgite powder is ground at a speed of 2000 rpm for 1-2 hours. The attapulgite crystals are fully dispersed through adsorption, electrochemical action and chemical reaction.

[0053] The present invention provides a composite hydrogel scaffold, which is prepared from the above 3D printing ink.

[0054] Furthermore, the composite hydrogel scaffold is manufactured from the above 3D printing ink by 3D printing or another rapid prototyping / solid free-form manufacturing process.

[0055] Preferably, the present invention provides a method for preparing a composite hydrogel scaffold, comprising 3D printing ink printing, specifically comprising the following steps:

[0056] 1) 3D printing ink prints out the required scaffold: Design a printing program, and 3D printing ink is used to print out the composite hydrogel scaffold layer by layer through a CF-300N extrusion needle under basic parameters (needle diameter: 0.1-1 mm; pressure: 0.1-0.8 MPa; feed rate: 0.5-5 cm / min);

[0057] Furthermore, the printing program is designed to construct the composite hydrogel scaffold using a 3D printer, such as a RegenHU biological 3D printer, according to actual needs, and the printing model is established by using AutoCAD and MaterialiseMimics combined with the 3D printer supporting software, and the parameters are set as a multi-layer three-dimensional structure, and the path gap and angle of each layer structure are adjusted as needed, and the printing program code is output after saving, and the designed model is imported into the printing program;

[0058] 2) cross-linking the printed scaffold with ultraviolet light of wavelength 360nm or 405nm for 10 to 100s to make the scaffold have a certain strength;

[0059] 3) placing the UV-crosslinked scaffold in a 0.05-0.2 mol / L crosslinking solution to continue crosslinking chitosan for 0.5-12 hours. After the reaction is completed, washing with anhydrous ethanol for multiple times to remove the oil phase, washing with ultrapure water for more than three times, and freeze-drying to obtain the crosslinking solution, wherein the crosslinking solution is any one of sodium hydroxide, glutaraldehyde, glyoxal, and catalase.

[0060] The present invention provides the use of the above-mentioned 3D printing ink, composite hydrogel scaffold or the 3D printing ink and composite hydrogel scaffold prepared by the preparation method for bone defect repair.

[0061] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0063] The present invention provides 3D printing ink, composite hydrogel scaffold, 3D printing ink preparation method, composite hydrogel scaffold preparation method and their application in bone defect repair. In order to further illustrate the present invention, the following embodiments and applications provided by the present invention are described in detail, but it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, which are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.

[0064] Example 1

[0065] Step 1: According to the mass / volume fraction, weigh 1g of strontium chloride (SrCl 2 ) particles were added to 10 mL of ATP suspension and stirred in a 37°C constant temperature water bath for 12 hours to mix evenly and allow the strontium ions to be fully adsorbed. Strontium-modified ATP (Sr-ATP) particles were collected by centrifugation. The particles were rinsed several times in distilled water to ensure complete removal of chlorite ions; then, AgNO was added to the suspension after rinsing. 3 The test was conducted to remove the residual chloride ions. The obtained product was dried at 100°C for two days and then crushed. The product was digested to obtain Sr-ATP powder;

[0066] Step 2: Take another 0.1g Sr-ATP powder, dissolve it in 10mL dodecane, and ultrasonicate it for 15min to evenly disperse the stable particles in the system. Vigorously stir it mechanically for 2min to completely emulsify it to obtain an oil phase; dissolve 0.1g GelMA in 1mL phosphate buffer solution at 60°C, add 0.05w / v% LAP photoinitiator, and mix and stir for 30min to obtain an aqueous phase. The oil phase and the aqueous phase are mixed in a volume ratio of 1:1, and the mixed system is vigorously mechanically stirred for 2min to completely emulsify it to obtain an oil-in-water Pickering emulsion.

[0067] Step 3: Weigh 0.01 g of chitosan and add it to 5 mL of Pickering emulsion, stir in a constant temperature water bath for 20 min, and stir the slurry evenly to obtain a mixed 3D printing ink, i.e., a composite hydrogel stock solution;

[0068] Step 4: Use the RegenHU biological 3D printer to build a printed scaffold. Use Auto CAD and MaterialiseMimics combined with the 3D printer supporting software to build a printing model. Set it to a 5-layer three-dimensional structure, the side length is set to 3mm, the path gap of each layer structure is set to 1.0mm spacing, and the printing angle is set to 45 degrees. After saving, output the printing program code, and import the designed model into the printing program;

[0069] Step 5: The 3D printing ink slurry is passed through a CF-300N extrusion needle to print out the hydrogel scaffold layer by layer under basic parameters (needle diameter: 0.2 mm; pressure: 0.5 MPa; feed rate: 0.5 cm / min).

[0070] Step 6: Cross-link the printed hydrogel scaffold using ultraviolet light with a wavelength of 405 nm for 10 seconds.

[0071] Step 7: Place the UV-crosslinked scaffold in a 0.05 mol / L sodium hydroxide solution to continue crosslinking chitosan for 0.5 h. After the reaction is completed, wash with anhydrous ethanol several times to remove the oil phase, shake and wash with ultrapure water on a shaker for more than three times, and dry with a freeze dryer to obtain a porous strontium-modified attapulgite hydrogel scaffold (Sr-ATP / GelMA / CS).

[0072] Example 2

[0073] Step 1: According to the mass / volume fraction, weigh 5g of strontium chloride (SrCl2) particles and add them to 20mL of ATP suspension. Stir in a constant temperature water bath at 37℃ for 20 hours to mix evenly so that strontium ions can be fully adsorbed. Collect the strontium-modified ATP particles (Sr-ATP) by centrifugation. Rinse the particles in distilled water several times to ensure that chlorite ions are completely removed; then add AgNO to the suspension after rinsing. 3 The product was dried at 100°C for two days and then crushed. The product was digested and the strontium content was tested by ICP-OES to obtain Sr-ATP powder.

[0074] Step 2: Take another 1g of Sr-ATP powder, dissolve it in 20mL of dodecane, and ultrasonicate it for 15min to evenly disperse the stable particles in the system. Vigorously stir it mechanically for 2min to completely emulsify it to obtain an oil phase; dissolve 0.5g of GelMA in 1mL of PBS solution at 60°C, add 0.05w / v% LAP photoinitiator, and mix and stir for 40min to obtain an aqueous phase. The oil phase and the aqueous phase are mixed in a volume ratio of 1:1, and the mixed system is vigorously mechanically stirred for 5min to completely emulsify it to obtain an oil-in-water Pickering emulsion.

[0075] Step 3: Weigh 0.1 g of chitosan and add it to 10 mL of Pickering emulsion, stir in a constant temperature water bath for 30 min, and stir the slurry evenly to obtain a printing mixed ink, that is, a composite hydrogel stock solution;

[0076] Step 4: Use the RegenHU biological 3D printer to build a printed scaffold for bone repair. Use Auto CAD and Materialise Mimics combined with the 3D printer supporting software to build a printing model. Set it to a 3-layer three-dimensional structure with a side length of 2 mm, a path gap of each layer of the structure set to 0.8 mm spacing, and a printing angle of 60 degrees. After saving, output the printing program code, and import the designed model into the printing program;

[0077] Step 5: The 3D printing ink slurry is passed through a CF-300N extrusion needle to print out the hydrogel scaffold layer by layer under basic parameters (needle diameter: 0.3 mm; pressure: 0.4 MPa; feed rate: 0.4 cm / min).

[0078] Step 6: The printed hydrogel scaffold was cross-linked using ultraviolet light with a wavelength of 405 nm for 20 min.

[0079] Step 7: Place the UV-crosslinked scaffold in a 0.1 mol / L sodium hydroxide solution to continue crosslinking chitosan for 1 hour. After the reaction is completed, wash with anhydrous ethanol several times to remove the oil phase, shake and wash with ultrapure water on a shaker for more than three times, and dry with a freeze dryer to obtain a porous strontium-modified attapulgite hydrogel scaffold (Sr-ATP / GelMA / CS).

[0080] Example 3

[0081] Step 1: According to the mass / volume fraction, weigh 8g of strontium chloride (SrCl 2 ) particles were added to 20 mL of ATP suspension and stirred in a 37°C constant temperature water bath for 24 hours to mix evenly and allow the strontium ions to be fully adsorbed. Strontium-modified ATP particles (Sr-ATP) were collected by centrifugation. The particles were rinsed several times in distilled water to ensure complete removal of chlorite ions; then, AgNO was added to the suspension after rinsing. 3 The product was dried at 100°C for two days and then crushed. The product was digested and the strontium content was tested by ICP-OES to obtain Sr-ATP powder.

[0082] Step 2: Take another 2g of Sr-ATP powder, dissolve it in 10mL of dodecane, and ultrasonicate it for 15min to evenly disperse the stable particles in the system. Stir it vigorously for 10min to completely emulsify it to obtain an oil phase; dissolve 1g of GelMA in 10mL of PBS solution at 60°C, add 0.05w / v% LAP photoinitiator, and stir it for 60min to obtain an aqueous phase. Mix the oil phase and the aqueous phase in a volume ratio of 1:1, stir the mixed system vigorously for 10min to completely emulsify it to obtain an oil-in-water Pickering emulsion.

[0083] Step 3: Weigh 0.1 g of chitosan and add it to 20 mL of Pickering emulsion, stir in a constant temperature water bath for 430 min, and stir the slurry evenly to obtain a printing mixed ink, that is, a composite hydrogel stock solution;

[0084] Step 4: Use the RegenHU biological 3D printer to build a scaffold for bone repair. Use Auto CAD and Materialise Mimics combined with the 3D printer supporting software to build a printing model. Set it to a 10-layer three-dimensional structure, the side length is set to 5mm, the path gap of each layer structure is set to 1.2mm spacing, the printing angle is set to 90 degrees, save it and output the printing program code, and import the designed model into the printing program;

[0085] Step 5: The 3D printing ink slurry is passed through a CF-300N extrusion needle to print out the hydrogel scaffold layer by layer under basic parameters (needle diameter: 0.15 mm; pressure: 0.5 MPa; feed rate: 0.3 cm / min).

[0086] Step 6: Cross-link the printed hydrogel scaffold using ultraviolet light at a wavelength of 405 nm for 30 seconds.

[0087] Step 7: Place the UV-crosslinked scaffold in a 0.2 mol / L sodium hydroxide solution to continue crosslinking chitosan for 12 hours. After the reaction is completed, wash with anhydrous ethanol several times to remove the oil phase, shake and wash with ultrapure water on a shaker for more than three times, and dry with a freeze dryer to obtain a porous strontium-modified attapulgite hydrogel scaffold (Sr-ATP / GelMA / CS).

[0088] Example 4

[0089] First, the hydrogel scaffold printed in Example 1 was placed in a well plate, and the bone marrow mesenchymal stem cell suspension was collected and inoculated in each scaffold area. Fresh culture medium was replaced every 24 hours, and then the culture medium was replaced every 2 days for further experiments. The microstructure and cell compatibility of the material were evaluated by scanning electron microscopy, cell Live / Dead staining, and phalloidin (FITC) staining. Figure 2 Live / Dead staining of cells is shown in Figure 3 , phalloidin staining Figure 4 .

[0090] The results showed that the composite hydrogel scaffold had a regular grid structure and uniform pore structure. Cells could grow, proliferate and spread well in the material, and the number of cells increased significantly over time. The results showed that the material had no immune response and toxic side effects with cells, showing good biocompatibility with cells.

[0091] Twelve clean-grade SD rats weighing 200-220 g were used to construct the skull defect model of SD rats. They were randomly divided into three groups: a sham operation group (blank group), a control group (unmodified group) and an experimental group (strontium-modified composite hydrogel scaffold group), with 4 rats in each group.

[0092] Example 5 (experimental group)

[0093] Clean-grade SD rats were anesthetized by injecting 3% sodium pentobarbital solution through the ear vein at a dosage of 30 mg / kg. All surgical instruments were disinfected in advance, and a skull defect model was made under a sterile environment. The defect hole specifications were diameter × thickness: 6 mm × 1 mm. After implanting strontium-modified attapulgite hydrogel scaffolds in clean-grade SD rats according to the pre-designed (raw materials and preparation methods are shown in Example 1. Unlike Example 1, the 3D printed model constructed in this embodiment is a 3D printed model adapted for skull defects), the wounds were sutured layer by layer, iodine was applied to the wounds, and sterilized gauze and bandages were used to fix the wounds. The rats were kept in a clean-grade environment after surgery, and penicillin was injected for 3 consecutive days after surgery. They were killed at 4 weeks, 8 weeks, and 12 weeks, respectively.

[0094] Comparative Example 1 (blank group)

[0095] Referring to Example 5, the difference from Example 5 is that the stent implanted in the blank group does not contain strontium-modified attapulgite.

[0096] Comparative Example 2 (group without strontium modification)

[0097] Referring to Example 5, the difference from Example 5 is that the stent implanted in the blank group uses attapulgite powder that has not been modified with strontium to replace Sr-ATP powder.

[0098] CT scanning, tissue section H&E and Masson staining were used to observe and comprehensively evaluate the repair effect of hydrogel materials on bone damage.

[0099] The results of H&E and Masson histological staining analysis showed that Figure 5 As shown in Figure 6, the results showed that there were no inflammatory cells at the host / material interface, and the bone repair material was gradually degraded and absorbed over time, and there was obvious new bone tissue.

[0100] The above animal experiments confirm that the strontium-modified attapulgite hydrogel scaffold prepared by the present invention has good porosity and the ability to induce bone regeneration, and also has strong mechanical support strength and biodegradability, and has the prospect of being widely used in clinical practice.

[0101] The raw materials of the bone repair composite hydrogel scaffold of the present invention are strontium-modified attapulgite, GelMA and chitosan, which are rich in sources, and all materials are non-toxic and have good biocompatibility. In addition, the present invention utilizes 3D bioprinting technology to construct a composite hydrogel scaffold material, which can maintain the high porosity and pore connectivity of the hydrogel, achieve a good match between the scaffold and the defect site, and better meet the needs of bone repair at the defect site. The above detailed description of the present invention is intended to enable people familiar with the technology in this field to understand the content of the present invention and implement it, and it cannot be used to limit the scope of protection of the present invention, and the present invention is not limited to the above-mentioned embodiments. All equivalent changes or modifications made according to the spirit of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A 3D printing ink, characterized in that: The invention comprises strontium-modified nano-attapulgite, methacrylated gelatin, a first phase solvent, a second phase solvent, a functional additive and a photoinitiator. The dosage ratio of the strontium-modified nano-attapulgite to the first phase solvent is 0.01-5 g / ml, the dosage ratio of the methacrylated gelatin to the second phase solvent is 0.01-0.5 g / ml, the photoinitiator is a LAP photoinitiator, the dosage ratio of the photoinitiator to the mixed solution of the methacrylated gelatin and the second phase solvent is 0.002-0.1 g / ml, the volume ratio of the total amount of the strontium-modified nano-attapulgite and the first phase solvent to the total amount of the photoinitiator, the methacrylated gelatin and the second phase solvent is 0.1:1-2:1, the functional additive is chitosan, the first phase solvent is any one of dodecane, octane, decane, cyclohexane, tetradecane and hexadecane, and the second phase solvent comprises a phosphate buffer.

2. A method for preparing 3D printing ink, characterized in that The following steps are involved: 1) According to the mass / volume fraction, 0.1 to 10 parts of strontium-modified nano-attapulgite powder are taken and dissolved in 10 to 500 parts of the first phase solvent, and ultrasonic treatment is performed for 15 minutes to uniformly disperse the stable particles in the system, and stirring is performed for 2 to 10 minutes to completely emulsify the particles; 2) Dissolve 0.1-10 parts of methacrylated gelatin in 1-100 parts of the second phase solvent solution at 60°C, add LAP photoinitiator in a ratio of 0.002-0.1 g / ml to the above mixed solution, and mix and stir for 30-60 minutes; 3) The mixed solution of step 1) and step 2) is mixed in a volume ratio of 0.1:1-2:1, and the mixed system is stirred for 2-10 minutes to completely emulsify it to obtain a water-in-oil Pickering emulsion; 4) According to the mass / volume fraction, weigh 0.01-1 part of chitosan particles and add them to 1-10 parts of Pickering emulsion, and stir in a constant temperature water bath for 20-40 minutes.

3. The method for preparing a 3D printing ink according to claim 2, characterized in that: The method also includes the steps of preparing the strontium-modified nano-attapulgite powder: According to the mass / volume fraction, 1 to 50 parts of strontium chloride particles are weighed and dissolved in 1 to 400 parts of nano-attapulgite suspension, stirred in a constant temperature water bath for 8-24 hours, evenly mixed, and the strontium-modified modified nano-attapulgite particles are collected by centrifugation. The particles are rinsed in distilled water, and AgNO3 is added to the suspension after rinsing for testing to remove residual chloride ions. The obtained product is dried at 100°C for two days and then crushed. The product is digested to obtain strontium-modified nano-attapulgite powder.

4. The method for preparing a 3D printing ink according to claim 3, characterized in that: The water used to dissolve the nano-attapulgite in the nano-attapulgite suspension is any one of deionized water, distilled water, phosphate buffer and physiological saline. The nano-attapulgite is 200-500 nanometer-scale crystal particles. Pure water is used as the grinding medium, sodium hexametaphosphate is used as the grinding aid and dispersant, and the attapulgite powder is ground at a speed of 2000 rpm for 1-2 hours. The attapulgite crystals are fully dispersed through adsorption, electrochemical action and chemical reaction.

5. A composite hydrogel scaffold, characterized in that: The 3D printing ink is prepared by the 3D printing ink according to claim 1 or the 3D printing ink preparation method according to any one of claims 2 to 4.

6. The method for preparing a composite hydrogel scaffold according to claim 5, characterized in that: The steps include: 1) 3D printing ink prints out the required scaffold: Design the printing program, and the 3D printing ink is passed through the CF-300N extrusion needle under the basic parameters: needle diameter: 0.1~1mm; pressure: 0.1~0.8MPa; feed rate: 0.5~5cm / min, and the composite hydrogel scaffold is printed layer by layer; 2) Cross-link the printed scaffold with ultraviolet light at a wavelength of 360 nm or 405 nm for 10 to 100 seconds; 3) placing the UV-crosslinked scaffold in a 0.05-0.2 mol / L crosslinking solution to continue crosslinking chitosan for 0.5-12 hours. After the reaction is completed, washing with anhydrous ethanol for multiple times to remove the oil phase, washing with ultrapure water for more than three times, and freeze-drying to obtain the crosslinking solution, wherein the crosslinking solution is any one of sodium hydroxide, glutaraldehyde, glyoxal, and catalase.

Citation Information

Patent Citations

  • PCL / GelMA biological porous scaffold based on Pickering emulsion and preparation method thereof

    CN114712566A

  • 3D printing Pickering emulsion ink co-stabilized by double nano particles as well as preparation method and application of 3D printing Pickering emulsion ink

    CN117551353A